A New Technique of Surface Anatomy MR Scanning of the Brain: Its Application to Scalp Incision Planning - Tsuchiya, Kazuhiro; Katase, Shichiro; Hachiya, Junichi; Hiyama, Takami; Shiokawa, Yoshiaki (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Surface anatomy scanning (SAS) is an established technique for demonstrating the brain's surface. We describe our experience in applying SAS with superposition of MR venograms to preoperative scalp incision planning.METHODS: In 16 patients, scalp incision planning was done by placing a water-filled plastic tube at the intended incision site when we performed SAS using half-Fourier single-shot fast spin-echo sequences. Two-dimensional phase-contrast MR angiograms were obtained to demonstrate the cortical veins and then superimposed upon the SAS images. The added images were compared with surgical findings using a four-point grading scale (0 to 3, poor to excellent).RESULTS: In each case, neurosurgeons could easily reach the lesion. Surgical findings correlated well with MR angiogram–added SAS images, with an average score of 2.56.CONCLUSION: Our simple technique is a useful means of preoperatively determining brain surface anatomy and can be used to plan a scalp incision site.